2017
DOI: 10.7899/jce-16-00013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interactive video test performance to overall class performance in a biomechanics course

Abstract: The results of this study did not support improved student assessment performance with incorporation of interactive video testing in the classroom environment. Continued research into new testing strategies is recommended to identify additional effective testing in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In the present study, there was a statistically significant difference between the two groups so the mean performance score was higher in the intervention group. As noted in other studies, and specifically described by Bennett [ 29 ], students reported that using video as a learning tool seemed more effective because they could easily see what was in the film. Descriptive studies and various expert opinions state that online learning is an important opportunity for students to enhance and support learning, so it helps to make this method work better.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, there was a statistically significant difference between the two groups so the mean performance score was higher in the intervention group. As noted in other studies, and specifically described by Bennett [ 29 ], students reported that using video as a learning tool seemed more effective because they could easily see what was in the film. Descriptive studies and various expert opinions state that online learning is an important opportunity for students to enhance and support learning, so it helps to make this method work better.…”
Section: Discussionsupporting
confidence: 52%
“…This is because in the Interactive Video uploaded to the LMS (learning management system) Moodle embeds an interactive learning component that stimulates students' thinking and encourages independent learning (Sinnayah et al, 2021). In addition, Interactive Video can stimulate cognitive and meta-cognitive (Bennett, 2017). The practicum is carried out to develop the performance skills of electrical measuring instruments, namely the use of a multimeter, to measure electric voltage, electric strength, and resistance in resistors.…”
Section: Effectiveness N-gain Test Resultsmentioning
confidence: 99%